Sunny Day : A Celebration of the Sesame Street Theme Song - Hart, Bruce; Stone, Jon R., 1959-; Raposo, Joe (New York : Random House, 2021)
Presents an illustrated celebration of the classic Sesame Street theme song.
Keywords: Childrens songs, English -- United States; Texts; Songs; Board books; Picture books